An audit of early complications after endonasal transsphenoidal resection of pituitary adenomas at Chris Hani Baragwanath Academic Hospital: a 5 year review of record - Mohale, Masedi Selby (University of the Witwatersrand, Johannesburg, 2023)
Background: Endoscopic endonasal transsphenoidal surgery (EETS) for pituitary adenomas is a common procedure done at Chris Hani Baragwanath Academic Hospital (CHBAH) due to a significant number of patients requiring the procedure at the institution. Post-transsphenoidal tumour resection complications may not be common but if unrecognised, they may result in significant morbidity and even mortality and hence it is of paramount importance to evaluate factors that may predict the occurrence of these various complications so as to improve vigilance and be able to monitor and manage them appropriately to avoid disastrous outcomes following EETS. However, there is no study has ever been conducted to clinically audit early complications associated with EETS at CHBAH. Even though literature suggests that complications associated EETS are not common. It is with outmost importance that they are monitored and managed appropriately as some of them may lead to chronic disability or death. Aim of the study: The aim of the study is to evaluate early complications following endoscopic endonasal transsphenoidal surgery of pituitary adenoma. Methodology: The study is a retrospective research study which evaluated early complications following EETS of PA at CHBAH. Also, investigated in this study was the factors that are associated with the occurrence of the complications, including the clinical outcomes following EETS. The study was a clinical audit that collected and analysed data from the medical records. Data was collected from medical records of patients with PAs who have undergone EETS’s from January 2016 until December 2020. CHBAH does an average of four EETS’s every month. A period of five years is defined as a suitable criterion for a clinical audit, and it is a reasonable period for a pool of study participants. The determination of sample size was performed in consultation with a biostatistician who recommended an estimated sample size of one hundred twenty (120). Descriptive analysis of all statistical data was analysed using Statistical Package for the Social Sciences (SPSS) version 24 (SPSS inc., Chicago, IL, USA). Results: The sociodemographic characteristics indicated that the majority of the study participants in non-functional PA group were males while the majority of the study participants in the functional pituitary adenoma group were females. The observation that there were more males than females in the non-functional pituitary adenoma group was expected, and the findings of the current study are in agreement with other several research studies. Also, the observation that there were more females in the functional pituitary adenoma group was not unexpected. These findings were also not surprising and were also in agreement with other previous studies. In bivariate analysis, study participants whose age were 20 - 40 years, and ages above 40 years were found be associated with the likelihood of occurrence of early complications of EETS of PA, including study participants whose tumour extensions were suprasella and parasella. These findings were not unexpected considering that prevalence of early complications vary depending on several factors, such as the size and location of the tumour, the experience and skill of the surgeon, and the patient's overall health status. Conclusion: The result of the current study confirms the notion that early complication of EETS of PA are rare.
A research report submitted in fulfilment of the requirement for the degree of Master of Medicine (Neurosurgery), in the Faculty of Health Sciences, School of Clinical Medicine at University of Witwatersrand, Johannesburg, 2023.
Keywords: Complications; Endonasal-Transsphenoidal Resection; Pituitary Tumours; Chris Hani Baragwanath Academic Hospital (CHBAH); Endoscopic endonasal transsphenoidal surgery (EETS); Pituitary Adenoma (PA); Suprasella; Parasella; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education